Anisotropy in hydraulic properties of unsaturated soils - Priono (2017)
Anisotropy has not been fully understood in the hydraulic properties of soil. The objective of this research is to investigate hydraulic anisotropy behavior, specifically the permeability and soil-water characteristic curve (SWCC) of soil. Two principal directions, i.e. the major (vertical-layering) and the minor (horizontal-layering), were investigated in compacted sand-kaolin specimens having different initial conditions and mica contents. Hydraulic anisotropy behavior of the specimens was observed under the saturated conditions and following the drying and wetting paths of unsaturated conditions using direct and indirect laboratory measurements. The results show that both the direct and indirect measurements agree on the observed hydraulic anisotropy values. Similar hydraulic anisotropy values are observed under the saturated conditions and the drying path of unsaturated conditions. Smaller values of hydraulic anisotropy are observed in the wetting path compared to those observed in the drying path of unsaturated conditions. In each drying and wetting path of unsaturated conditions, the observed hydraulic anisotropy values are consistent for all applied matric suctions. In addition, each drying and wetting SWCC should be considered as a scalar property of the soil.